A comprehensive review on integrated photo rechargeable batteries- supercapacitors, and their techno-economic feasibility - Jyoti Bhattacharjee; Subhasis Roy (Journal of Photochemistry and Photobiology)
Solar energy is a cost-effective replacement for traditional fossil fuels since it is a green, renewable energy source. Direct solar energy conversion and storage using electrochemistry have been proposed. In this context, the need to create high-performance integrated devices based on solar energy conversion components such as solar cells, photoelectrodes, and electrochemical energy storage components has increased. Carbon and functional materials based on carbon play a major role in the performance of energy conversion/storage components. The techno-economic performance of two alternative hybrid energy storage system designs of the supercapacitor and photo rechargeable battery systems are compared in this review paper. The importance and impact of photoactive nanomaterials acting as photoelectrodes in embedded photo batteries result from their structure, topology, and pertinent for photo charging and Li-ion storage; this photo battery uses highly photosensitive two-dimensional lead halide perovskites. Integrating lithium-ion batteries (LIB) with fast-charging supercapacitors (SCs) decreases the time storage technologies take compared to conventional systems. The important role of carbon‐based materials in integrated devices has been highlighted. The optimized electric renewable model was used to analyze the techno-economic analysis of the fast-charging lithium-ion battery (FCLIB) proposal. The fundamentals of integrated devices are presented, emphasizing the functions performed by carbon-based materials in these hybrid energy devices. This review also highlights the importance of integrated devices, photovoltaic and photoelectrochemical rechargeable batteries, and supercapacitors and their techno-economic viability, challenges, and future development.